2019
DOI: 10.3390/geosciences10010009
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Entrainment and Deposition Models in Avalanche Simulations from High-Resolution Radar Data

Abstract: Depth-integrated simulations of snow avalanches have become a central part of risk analysis and mitigation. However, the common practice of applying different model parameters to mimic different avalanches is unsatisfying. In here, we analyse this issue in terms of two differently sized avalanches from the full-scale avalanche test-site Vallée de la Sionne, Switzerland. We perform depth-integrated simulations with the toolkit OpenFOAM, simulating both events with the same set of model parameters. Simulation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…The small estimated values of the mean deposition speed for the bedload can be explained by the combination of deposition and erosion processes (cf. Parker et al 1986;Cao et al 2004;Trinh et al 2017;Rauter and Köhler 2020). The experimental observations showed that saltating/rolling of particles occurred in the bedload (Brosch and Lube 2020); the saltating/rolling of particles accompany a complicated combination of deposition and erosion processes.…”
Section: Discussionmentioning
confidence: 99%
“…The small estimated values of the mean deposition speed for the bedload can be explained by the combination of deposition and erosion processes (cf. Parker et al 1986;Cao et al 2004;Trinh et al 2017;Rauter and Köhler 2020). The experimental observations showed that saltating/rolling of particles occurred in the bedload (Brosch and Lube 2020); the saltating/rolling of particles accompany a complicated combination of deposition and erosion processes.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that depth averaged model approaches do not provide any vertical velocity information and are therefore unable of reproducing turbulent structures resulting in large local velocity variations, that are particularly interesting in the frontal region of the avalanche [52]. The challenge of properly considering velocities in avalanche simulation evaluations has been previously debated yielding similar results [29,30] and new, promising measurement [53] and evaluation approaches [54] are currently discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rauter and Köhler (2019) proposed an empirical deposition model, which is here rewritten for a mass block (i.e. neglecting the pressure gradient term):…”
Section: Dense-core Deposition Modelmentioning
confidence: 99%